Manual didáctico para la creación de personajes con animación 2D, para incentivar la creatividad de niños con TDAH. - Flores Zavala, Jessica Morelia (2026)
This research arises from the need to create educational materials that foster creativity in children aged 8 to 10 with "Attention Deficit Hyperactivity Disorder” (ADHD), a group that faces difficulties adapting to conventional teaching methods. The main objective was to develop a pedagogical manual for character creation, considering the attention and learning factors specific to this group and integrating pedagogical concepts, accessible methodologies, and graphic design principles. The study follows a qualitative, descriptive, and project-based approach grounded in Robert Scott's methodology, which structures the design process into four stages: identification of needs, visual conceptualization, resource selection, and technical implementation. A bibliographic analysis was conducted on ADHD, child creativity, 2D animation as a pedagogical tool, and the development of educational materials. The manual was validated through Likert-scale surveys completed by three educational and psychopedagogical professionals, as well as an interview with an experienced graphic designer. The results showed strong agreement regarding the pedagogical value and creative relevance of the proposal, with high reliability (Cronbach's alpha = 0.860). The final manual consists of 60 pages divided into four progressive workshops, emphasizing legibility, visual simplicity, conceptual coherence, and user-centered design. This research addresses a need within the Ecuadorian educational system for inclusive tools aligned with Sustainable Development Goal 4 (Quality Education) and the principles of neurodiversity, highlighting the creative strengths of children with ADHD rather than focusing solely on their challenges.